2017
DOI: 10.1097/ccm.0000000000002515
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and Benzodiazepines Associated With Prolonged ICU Stay in Critically Ill Infants and Young Children*

Abstract: Objectives: Delirium is prevalent among critically ill children, yet associated outcomes and modifiable risk factors are not well defined. The objective of this study was to determine associations between pediatric delirium and modifiable risk factors such as benzodiazepine exposure and short-term outcomes. Design: Secondary analysis of collected data from the prospective validation study of the Preschool Confusion Assessment Method for the ICU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 44 publications
3
117
0
2
Order By: Relevance
“…Sepsis is also a risk factor for ICU-acquired weakness and delirium [7][8][9]. Many of these hospital-acquired complications may contribute to a septic patient's prolonged ICU stay [10][11][12], increasing the chance of developing PCI. Thus, the development of PCI in patients with sepsis is of special interests.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is also a risk factor for ICU-acquired weakness and delirium [7][8][9]. Many of these hospital-acquired complications may contribute to a septic patient's prolonged ICU stay [10][11][12], increasing the chance of developing PCI. Thus, the development of PCI in patients with sepsis is of special interests.…”
Section: Introductionmentioning
confidence: 99%
“…As DS patients have more complex recoveries than normal, it is entirely possible that any recovery lengthened by DS complications will require more sedatives that, in turn, will increase withdrawal symptoms after prolonged usage. Furthermore, a recent study showed that MDZ usage is a risk factor for developing pediatric delirium 38 . Taken together, these results pair well with our results and indicate that a new approach to sedation in DS patients is required.…”
Section: Discussionmentioning
confidence: 99%
“…10 No such evidence yet exists in PICU cohorts; some PICU studies demonstrate an association between delirium and infection, [11][12][13] and others do not. [14][15][16] Anticholinergic medications have been associated with increased risk of delirium in several PICU cohorts. 13,16 Measures of anticholinergic medication burden have been used extensively in the adult literature, and have been associated with quantitative measures of anticholinergic activity such as the SAA.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Anticholinergic medications have been associated with increased risk of delirium in several PICU cohorts. 13,16 Measures of anticholinergic medication burden have been used extensively in the adult literature, and have been associated with quantitative measures of anticholinergic activity such as the SAA. 17 One of the most commonly used scores is the anticholinergic drug scale (ADS), which rates individual medications using a variety of characteristics, including any known anticholinergic properties from pharmacological receptor-binding studies, known anticholinergic adverse events, or consensus expert opinion.…”
Section: Introductionmentioning
confidence: 99%